STRATEGI PENERAPAN E-COMMERCE DALAM MENINGKATKAN KEUNGGULAN BERSAING - I Made Adi Pranata; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2014)
Technology is developing so rapidly should be used by businesses. Appropriate useof technology can improve the performance of the company. Business process is lengthy,complicated and takes a long time to become more efficient and help reduce costs. E-commerceis one of the technologies that should be implemented in the company. E-commerce is theanswer to the demands of globalization.Growth of Internet users is growing rapidly should be the reason why the companyshould try to implement e-commerce. Although it is the development of e-commerce users havenot been so impressive compared to the growth of internet users. The phenomenon of ecommercecan’t be understood and well-supported, especially in developing countries such asIndonesia. Consumers do not have confidence in the security of transactions, products shownsimilarities with reality, to the consumer who does not have the ability to do so.Application of e-commerce will be able to increase the competitive advantage of thecompany. Implementation of e-commerce requires a careful strategy that has been decided bythe management of the company, including preparing the resources and technology toolscapable human resources in the field of information technology, building information systemsfor managing the company's operations. Mechanisms and transaction services are fast andshort with good security. Establish good cooperation with suppliers and distributors. If all ofthe above can be done well will be able to increase the competitive advantage of the company.Keywords: E-commerce, business strategy, competitive advantage